Switchable organoplatinum metallacycles with high quantum yields and tunable fluorescence wavelengths - Jun-Long Zhu (Nature Portfolio, 2019)
Fluorescent supramolecular coordination complexes are of interest for chemical sensing and optical devices. Here the authors synthesize nine organoplatinum metallacycles with high quantum yields, whose fluorescence wavelengths are tuned through manipulation of their photoinduced electron transfer and intramolecular charge transfer properties.